Phenoxycarboxylic acid herbicides in environment: Recent updates on pretreatment and analysis methods - Chen-jie Ren; Yuan Zhang; Yu Bian; Juan Zhu; Xue-song Feng; Kun Liu (Ecotoxicology and Environmental Safety, 2025)
Phenoxycarboxylic acid herbicides (PCAs), including 2,4-D and MCPA, are recognized as auxin herbicides renowned for their proficient management of grass weeds. However, the extended environmental longevity of PCAs presents ecological concerns and potential health risks. Therefore, the assessment of PCAs in environmental samples is of paramount significance. To date, no comprehensive review has addressed the pretreatment and analytical methods for PCAs since 2017. This review aims to provide a systematic overview of the techniques developed for PCA residue analysis over the past years. This work particularly highlights recent advancements in novel pretreatment techniques, materials, and analytical strategies, being committed to presenting insights based on conventional approaches. Pretreatment strategies include liquid-liquid extraction, and solid-phase extraction, as well as emerging technologies such as microextraction-based methods, magnetic-assisted methods, and so on. Special emphasis is placed on the integration of cutting-edge materials such as molecularly imprinted polymers and nanomaterials, and on the adoption of unconventional solvents like ionic liquids and supramolecular solvents, which have significantly enhanced selectivity, sensitivity, and environmental compatibility. High-performance liquid chromatography-tandem mass spectrometry continues to serve as a prevalent method of detection. Furthermore, gas chromatography-based methods, capillary electrophoresis methods, and sensor methods have been utilized for the analysis of PCAs. This work provides a comparative evaluation of these techniques based on their practical applicability, analytical performance, and sustainability, thereby identifying current limitations and future opportunities for PCA residue analysis.